Centering the Strengths of American Indian Culture, Families and Communities to Overcome Type 2 Diabetes - Walls, Melissa; Chambers, Rachel; Begay, Marissa; Masten, Kristin; Aulandez, Kevalin; Richards, Jennifer; Gonzalez, Miigis; Forsberg, Angie; Nelson, Leonela; Larzelere, Francene; McDougall, Cindy; Lhotka, Megan; et al. (Frontiers in Public Health, 2022)
Type 2 diabetes (T2D) is a critical Indigenous health inequity rooted in experiences of colonization and marginalization including disproportionate exposure to stressors, disruption of traditional family and food systems, and attacks on cultural practices that have led to more sedentary lifestyles. Thus, an important step in redressing inequities is building awareness of and interventions attuned to unique Indigenous contexts influencing T2D and Indigenous culture as a pathway to community wellbeing. Using a dynamic, stage-based model of intervention development and evaluation, we detail the creation and evolution of a family-based, culturally centered T2D preventive intervention: Together on Diabetes (later Together Overcoming Diabetes) (TOD). The TOD program was built by and for Indigenous communities via community-based participatory research and has been implemented across diverse cultural contexts. The TOD curriculum approaches health through a holistic lens of spiritual, mental, physical and emotional wellness. Preliminary evidence suggests TOD is effective in reducing diabetes risk factors including lowering BMI and depressive symptoms, and the program is viewed favorably by participants and community members. We discuss lessons learned regarding collaborative intervention development and adaptation across Indigenous cultures, as well as future directions for TOD.